2018
DOI: 10.2174/1570159x16666171206144045
|View full text |Cite
|
Sign up to set email alerts
|

Glaucoma and Alzheimer Disease: One Age-Related Neurodegenerative Disease of the Brain

Abstract: In conclusion, preclinical and clinical evidence gathered so far support the notion that glaucoma is a widespread neurodegenerative condition whose common pathogenetic mechanisms with other diseases, i.e. Alzheimer Disease, should be further investigated as they may shed new light on these diseases improving both diagnosis and treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
104
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(106 citation statements)
references
References 83 publications
1
104
0
1
Order By: Relevance
“…Moreover, various eye-specific pathologies such as AMD and glaucoma share characteristics of other CNS pathologies. [3][4][5][6] Similarities in the structure of senile plaques observed in Alzheimer's disease (AD) with drusen in AMD have been demonstrated, and it has been suggested that AMD pathophysiology may have common molecular pathways with neurodegenerative disorders of the CNS. [4][5][6] Neurotrophic factors are a class of regulatory proteins of nervous tissue that promote the proliferation, differentiation, and functioning of neurons and protect them from apoptosis.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, various eye-specific pathologies such as AMD and glaucoma share characteristics of other CNS pathologies. [3][4][5][6] Similarities in the structure of senile plaques observed in Alzheimer's disease (AD) with drusen in AMD have been demonstrated, and it has been suggested that AMD pathophysiology may have common molecular pathways with neurodegenerative disorders of the CNS. [4][5][6] Neurotrophic factors are a class of regulatory proteins of nervous tissue that promote the proliferation, differentiation, and functioning of neurons and protect them from apoptosis.…”
Section: Resultsmentioning
confidence: 99%
“…Firstly, the age of glaucoma onset is relatively earlier than the age of dementia occurrence, for which the follow up period of the current study might be inadequate [1,15]. On the other hand, the current study included multiple covariates that would lead to the development of dementia in the regression analysis, while the previous study only compared the relationship between glaucoma and dementia with a small study population [17]. Further study is suggested to investigate this issue more completely.…”
Section: Discussionmentioning
confidence: 89%
“…Several researchers have discussed the relationship between dementia and eye diseases [17,31,32]. In one study, the percentage of glaucoma was significantly higher in those with dementia, and vice versa [17]. Another retrospective study illustrated that OAG was associated with AD but not PD [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A few candidate analytes for vaccine have already been indicated in literature for AD. The notion that AD is etiopathogenically similar to glaucoma [90][91][92][93] bolsters the aim of testing the same list on RGCs as well. Factors such as brain-derived neurotrophic factor and ciliary neurotrophic factor are potential candidates for this approach.…”
Section: Glaucoma Where No Gene Is Known To Be Mutatedmentioning
confidence: 99%